Giving from the Heart: The Role of the Heart and the Brain in Virtuous Motivation and Integrity - Karns, Christina; Skorburg, Joshua (My University, 2016)
To what extent and in what way is the self unified?  How does its degree of unification lead to or stymie virtuous motivation and action?  This project investigates embodied fluency in value-directed-actions and a drive toward integrity – an alignment between our explicitly endorsed values and automatic responses or actions. Our conceptual model operationalizes integrity as the interaction between implicit associations and automaticity of virtuous actions with self-reported explicit values endorsed by the self, with embodied responses serving as a mediator between integrity and behavior. Prediction 1: If generous values are explicitly endorsed by the self, then generous values should predict deliberative giving behavior. Prediction 2: If generous values are or have become habituated and automatic in some individuals, then implicit associations should predict automatic giving behavior. Prediction 3: Embodied measures of autonomic stress responses and neural reward will assess separate aspects of acting in accord with values. In addition to testing the local associations between measurement domains, the multimodal dataset we will acquire (self-report, implicit association tests, response times, autonomic physiology, electroencephalography) will allow us to statistically test our initial working model of integrated virtue. In this presentation, we will address our progress on data acquisition as well as our progress on a collaborative theory paper. We will reflect on the development of our project from the initial proposal, through feedback from the SMV core project team, up to the present data acquisition and analysis stage and discuss specific issues - both challenging and promising -  that have cropped up in this development, as well as some broader themes for research at the interface of neuroscience and moral philosophy.
This presentation was delivered on May 7, 2016 by Dr. Christina Karns and Mr. Joshua Skorburg at the 2016 Self, Motivation, and Virtue Conference, held at the University of Notre Dame, South Bend, Indiana.
Keywords: Psychology; Psychology, Cognitive.